2020
DOI: 10.3390/jcm9061684
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Neuro-Psychotherapy Treatment to Foster the Adjustment in Acquired Brain Injury Patients—A Randomized Controlled Study

Abstract: Adjustment disorders (AjD) with depressive symptoms following an acquired brain injury (ABI) is a common phenomenon. Although brain injuries are increasing more and more, research on psychological therapies is comparably scarce. The present study compared, by means of a randomized controlled trial (RCT), a newly developed integrative treatment (Standard PLUS) to a standard neuropsychological treatment (Standard). Primary outcomes were depressive symptoms assessed with the Beck Depression Inventory (BDI-II) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…Relationship quality was assessed with two measures: the 15-item Mutuality Scale (MS; Archbold et al, 1990) and the 7-item Relationship Assessment Scale (RAS; Hendrick, 1988), both of which have been demonstrated to be reliable and valid in research studies with stroke dyads (Pucciarelli et al, 2016; Urech et al, 2020). MS items are rated on a 5-point scale ranging from not at all to a great deal , with higher scores representing higher relationship quality.…”
Section: Methodsmentioning
confidence: 99%
“…Relationship quality was assessed with two measures: the 15-item Mutuality Scale (MS; Archbold et al, 1990) and the 7-item Relationship Assessment Scale (RAS; Hendrick, 1988), both of which have been demonstrated to be reliable and valid in research studies with stroke dyads (Pucciarelli et al, 2016; Urech et al, 2020). MS items are rated on a 5-point scale ranging from not at all to a great deal , with higher scores representing higher relationship quality.…”
Section: Methodsmentioning
confidence: 99%
“…Although still sparsely represented, psychotherapeutic interventions for patients with acquired brain injury have emerged in the last decade 12 15 . Effective approaches include positive psychotherapy 13 , integrative neuro-psychotherapy incorporating interventions of cognitive behavioral therapy 12 , acceptance and commitment therapy 14 as well as compassion-focused therapy 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although still sparsely represented, psychotherapeutic interventions for patients with acquired brain injury have emerged in the last decade 12 15 . Effective approaches include positive psychotherapy 13 , integrative neuro-psychotherapy incorporating interventions of cognitive behavioral therapy 12 , acceptance and commitment therapy 14 as well as compassion-focused therapy 15 . Research shows that psychotherapy can help to ameliorate the adjustment-process to acquired brain injury 16 and promising evidence summarizes the effectiveness of psychological interventions for patients with acquired brain injury on depressive symptoms with an overall medium effect size of d = 0.69 when compared to control conditions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study demonstrated the beneficial and stable long-term effects of holistic neuropsychological rehabilitation but also highlighted some areas that require further consideration (Shany-Ur et al 2020 ). Similar studies have found positive effects of holistic rehabilitation on psychological, emotional, and quality of life measures, although the benefits on cognitive functions have been mixed (Afsar et al 2021 ; Exner et al 2021 ; Holleman et al 2018 ; Nilsson et al 2011 ; Sarajuuri et al 2018 ; Urech et al 2020 ).…”
Section: Holistic Approachmentioning
confidence: 85%